INCREASING THE EFFICIENCY OF THE TREASURER'S WORK THROUGH THE MATCHING OF NIK AND NPWP IN THE ENVIRONMENT OF SEMARANG STATE UNIVERSITY - Festi Zulfaturrohmah; Julius Pungky Wasono; Kris Brantas Abiprayu; Dheasey Amboningtyas (Forum Ilmu Sosial, 2024)
The goal of this study is to provide all taxpayers in the Semarang State University region with up-to-date information on the policies of the Directorate General of Taxation (DGT). This will enable them to provide their opinions and justifications for fulfilling their individual tax obligations through matching NIK and NPWP, thereby increasing the treasurer's capacity for activity. This study employs a quantitative technique and survey procedures to conduct descriptive research. Basic information was utilized in the research. The data from this study shows that 200 WPOP employees of Semarang State University completed the questionnaires, which were distributed to them directly beginning on January 2, 2024. There were 200 respondents, according to the information the researchers received after distributing the questionnaire. PLS SEM will be used to process the information. Since distribution was done directly in this study, it is a mix method study using both quantitative and qualitative data. And that is to choose a sample from the population that was obtained, which consists of workers in the Semarang State University Area who range in age from 20 to 50. According to the study's findings, the NIK and NPWP matching from the treasurer's socialization is suitable and complies with the rules.